Interferon regulates neural stem cell function at all ages by orchestrating mTOR and cell cycle - Damian Carvajal Ibañez; Maxim Skabkin; Jooa Hooli; Santiago Cerrizuela; Manuel Göpferich; Adrien Jolly; Katrin Volk; Marc Zumwinkel; Matilde Bertolini; Gianluca Figlia; Thomas Höfer; Guenter Kramer; et al. (EMBO Molecular Medicine)
Abstract Stem cells show intrinsic interferon signalling, which protects them from viral infections at all ages. In the ageing brain, interferon signalling also reduces the ability of stem cells to activate. Whether these functions are linked and at what time interferons start taking on a role in stem cell functioning is unknown. Additionally, the molecular link between interferons and activation in neural stem cells and how this relates to progenitor production is not well understood. Here we combine single‐cell transcriptomics, RiboSeq and mathematical models of interferon to show that this pathway is important for proper stem cell function at all ages in mice. Interferon orchestrates cell cycle and mTOR activity to post‐transcriptionally repress Sox2 and induces quiescence. The interferon response then decreases in the subsequent maturation states. Mathematical simulations indicate that this regulation is beneficial for the young and harmful for the old brain. Our study establishes molecular mechanisms of interferon in stem cells and interferons as genuine regulators of stem cell homeostasis and a potential therapeutic target to repair the ageing brain.